2011
DOI: 10.3945/ajcn.110.004580
|View full text |Cite
|
Sign up to set email alerts
|

Playing a computer game during lunch affects fullness, memory for lunch, and later snack intake

Abstract: These findings provide further evidence that distraction during one meal has the capacity to influence subsequent eating. They may also help to explain the well-documented association between sedentary screen-time activities and overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 33 publications
5
87
0
3
Order By: Relevance
“…If attention is drawn away from eating by providing participants with the opportunity to watch television or play a computer game while eating, these distracted participants will eat more later than participants who were not distracted during eating (Oldham-Cooper, Hardman, Nicoll, Rogers, & Brunstrom, 2011;Higgs & Woodward, 2009;Mittal, Stevenson, Oaten, & Miller, 2011). Conversely, if participants are encouraged to focus on food while they are eating then they will eat less than participants who were asked to eat as usual (Higgs & Donohoe, 2011;Robinson, Kersbergen, & Higgs, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…If attention is drawn away from eating by providing participants with the opportunity to watch television or play a computer game while eating, these distracted participants will eat more later than participants who were not distracted during eating (Oldham-Cooper, Hardman, Nicoll, Rogers, & Brunstrom, 2011;Higgs & Woodward, 2009;Mittal, Stevenson, Oaten, & Miller, 2011). Conversely, if participants are encouraged to focus on food while they are eating then they will eat less than participants who were asked to eat as usual (Higgs & Donohoe, 2011;Robinson, Kersbergen, & Higgs, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…Exemplo disso seria a pergunta referente ao consumo de embutidos, na qual foram listados oito alimentos. Outro motivo poderia ser a dificuldade de o aluno informar a ingestão de determinados alimentos em função de consumi-los frequentemente enquanto realiza outra atividade, como, por exemplo, enquanto assiste à TV ou joga videogame 31,32 . Um terceiro motivo poderia ser a dificuldade de diferenciar os itens contemplados na questão referente a biscoitos salgados daqueles abarcados na questão sobre salgadinhos de pacote por não saberem a diferença entre os dois termos.…”
Section: Análise Dos Dadosunclassified
“…Moray et al (2007) also concluded that estimates of food intake were less accurate if participants were watching television whilst eating. In a similar vein research indicates that many other factors may distract from eating including listening to a story (Bellisle and Dalix, 2001;Long et al, 2011), listening to music (Stroebele and de Castro, 2006), playing a computer game (Oldham-Cooper et al, 2011) and engaging in a word counting task (Boon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moray et al (2007) also concluded that estimates of food intake were less accurate if participants were watching television whilst eating. In a similar vein research indicates that many other factors may distract from eating including listening to a story (Bellisle and Dalix, 2001;Long et al, 2011), listening to music (Stroebele and de Castro, 2006), playing a computer game (Oldham-Cooper et al, 2011) and engaging in a word counting task (Boon et al, 2002).Research has also explored the ways in which aspects of the food environment can distract an individual making it easier to overeat and harder to monitor how much is being consumed (Fisher, Rolls and Birch, 2003;Rozin, Dow, Moscovitch and Rajaram, 1998;Wansink, 2004). For example, a multitude of studies indicate that over eating can be 4 triggered by factors such as the ambience of the room, container size, plate size, variety of food and perceived time of day (Stroebele and de Castro, 2004;Wansink, Painter and Lee, 2006; Wansink, van Ittersum and Painter, 2006;Wansink and Park, 2001).…”
mentioning
confidence: 98%